Thrust-related metamorphism in Carboniferous slates of southern Patagonia (South America): The fate of forearc successions. - Suárez, Rodrigo (2024)
Fil: Suárez, Rodrigo. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología, Río Negro, Argentina